Inhibition of phage-resistant bacterial pathogen re-growth with the combined use of bacteriophages and EDTA. (December 2021) - Huang, Hung-Hsin; Furuta, Munenori; Nasu, Takayuki; Hirono, Miku; Pruet, Jaroenkolkit; Duc, Hoang Minh; Zhang, Yu; Masuda, Yoshimitsu; Honjoh, Ken-ichi; Miyamoto, Takahisa
Abstract: The combined effects of ethylenediaminetetraacetic acid (EDTA) and bacteriophage (phage) treatment of foodborne pathogens were investigated. Although viable counts for Campylobacter jejuni decreased by 1.5 log after incubation for 8 h in the presence of phage PC10, re-growth was observed thereafter. The combination of phage PC10 and 1 mM EDTA significantly inhibited the re-growth of C. jejuni . The viable counts for C. jejuni decreased by 2.6 log ( P < 0.05) compared with that of the initial count after 24 h. Moreover, EDTA at 0.67 or 1.3 mM, combined with the specific lytic phages, also effectively inhibited the re-growth of phage-resistant cells of Campylobacter coli, Salmonella enterica serovar Enteritidis, and Salmonella enterica serovar Typhimurium . In addition, the combined effects of lytic phages and EDTA were investigated on the viability of Campylobacter in BHI broth at low temperatures followed by the optimum growth temperature. The re-growth of C. coli was significantly inhibited by the coexistence of 1.3 mM EDTA, and the viable counts of surviving bacteria was about the same as the initial viable count after the incubation. This is the first study demonstrating the combined use of lytic phages and EDTA is effective in inhibiting the re-growth of phage-resistant bacteria in Gram-negative bacteria. Highlights: Combination of lytic phages and EDTA inhibited the re-growth of phage resistant bacteria. Chelation of Mg 2+ by EDTA seems important for the combined effects with phages. Phages decreased viability of Campylobacter at low temperature and inhibited the re-growth in combination with EDTA.